Non-EFL Learners’ Perceived Benefits and Limitations of Exploring Chatbots in Academic Writing Class - Azzahra, Zaida Azzahra; Daniel Ari Widhiatama (Inspiring: English Education Journal, 2025)
Chatbot integration in Language Education using chatbots shows potential to improve students’ writing skills. This study explores the benefits and limitations of using chatbots in academic writing classes for non-EFL students, specifically Agrotechnology students at Universitas Mercu Buana Yogyakarta. This study uses qualitative research data collected through classroom observations and semi-structured interviews over a semester. The observations focused on how students use chatbots to produce academic essays in Academic Writing classes. Semi-structured interviews were conducted with five students. Interview participants were selected based on their relevance to the research scope, ensuring that their responses aligned with the study's objectives while maintaining a focused and manageable range of inquiry. This study concludes that integrating chatbots and manual validation to ensure depth and critical thinking in writing classes using chatbots for non-EFL students is beneficial in developing writing skills that support their foreign language development.